Spreading further: the first record of the alien bivalve Theora lubrica in the Southwestern Atlantic Ocean - Machado, Fabrizio Marcondes; Suga, Cristiane Midori; Onodera, Fabio Kiyoshi Camara; Melo, Mariana Sousa; Viti, Thais; Cavinatto, Vilma Maria; Lammardo, Ana Carolina da Rocha; Yonamine, Carolina Yumi; Sáfadi, Regina Sawaia; Nogueira-Junior, Luis Antonio; Oliva, Luiz Fernando Maciel (Frontiers in Marine Science, 2025)
Biological invasions are globally recognized as one of the main drivers of biodiversity loss. Over the past four decades, there has been significant progress in understanding the mechanisms of alien species introduction into marine and estuarine environments. It is currently known that although humans can spread non-native species in various ways (e.g. aquaculture, vessel biofouling and oil and gas activities), ballast water is one of the most effective being considered one of the main threats to marine biodiversity. This pathway also appears to be the main transport vector to explain the spread of the exotic bivalve Theora lubrica (or Asian Semele) since the late 1950s. In this study, we report for the first time the presence of Asian Semele in the Southwestern Atlantic, specifically along the Southeast coast of Brazil. Furthermore, we also provide new insights into shell morphology, gross anatomy and ecological aspects, as well as the updated global distribution of this invasive alien species.